BLENDERS OF PERIODIC ACTION FOR PREPARATION OF THE BAR SANDY-RESIN MIXTURES - B. V. Kurakevich; A. P. Melnikov; T. S. Mileeva; L. R. Sysojeva; A. V. Pashkevich (Литьë и металлургия)
The technical parameters of batch mixers for preparation of the sand mixtures of different application are given.